Mosaic Down Syndrome with Chronic Myeloid Leukemia: A Case Report (Bangladesh Journal of Anatomy, 2013)
DOI: http://dx.doi.org/10.3329/bja.v9i2.15285 Bangladesh Journal of Anatomy 2011 Vol.9(2) pp.119-121